Global scales for cognitive screening in Parkinson's disease: Critique and recommendations. Issue 2 (23rd November 2017) - Skorvanek, Matej; Goldman, Jennifer G.; Jahanshahi, Marjan; Marras, Connie; Rektorova, Irena; Schmand, Ben; van Duijn, Erik; Goetz, Christopher G.; Weintraub, Daniel; Stebbins, Glenn T.; Martinez‐Martin, Pablo; ,
Abstract: Background: Cognitive impairment is a common nonmotor manifestation of Parkinson's disease, with deficits ranging from mild cognitive difficulties in 1 or more of the cognitive domains to severe dementia. The International Parkinson and Movement Disorder Society commissioned the assessment of the clinimetric properties of cognitive rating scales measuring global cognitive performance in PD to make recommendations regarding their use. Methods: A systematic literature search was conducted to identify the scales used to assess global cognitive performance in PD, and the identified scales were reviewed and rated as "recommended, " "recommended with caveats, " "suggested, " or "listed" by the panel using previously established criteria. Results: A total of 12 cognitive scales were included in this review. Three scales, the Montreal Cognitive Assessment, the Mattis Dementia Rating Scale Second Edition, and the Parkinson's Disease‐Cognitive Rating Scale, were classified as "recommended." Two scales were classified as "recommended with caveats": the Mini‐Mental Parkinson, because of limited coverage of executive abilities, and the Scales for Outcomes in Parkinson's Disease‐Cognition, which has limited data on sensitivity to change. Six other scales were classified as "suggested" and 1 scale as "listed." Conclusions: Because of the existence of "recommended" scales for assessment of global cognitive performance in PD, this task force suggests that the development of a new scale for this purpose is not needed at this time. However, global cognitive scales are not a substitute for comprehensive neuropsychological testing. © 2017 International Parkinson and Movement Disorder Society